BARRE, VERMONT, CHARTER AND ORDINANCES OF THE CITY, ch. 38, § 7 at 116, 117 (1904 Vermont Watchman Co.) (Passed 1895). - (:unkn) unknown (My University, 1895)
No person shall carry within the city any steel or brass knuckles, pistol, slung shot, stilletto, or weapon of similar character, nor carry any weapon concealed on his person without permission of the mayor or chief of police in writing."
Keywords: CARRY